APPLYING PICTURE IN INCREASING STUDENT’S VOCABULARY AT THE FIRST GRADE OF JUNIOR HIGH SCHOOL 3 TONDANO - Korompis, Christy Gloria; Tuna, Jim R.; Kumayas, Tirza (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This research investigates whether teaching English Vocabulary by applying picture can increase students’ vocabulary or not. The population of this study is students in 2022, in seventh grade of SMP Negeri 3 Tondano. The writer took one class to be the sample. Students consist of twenty four students (n=24). The writer used pre-experimental design with pre-test and post-test. The pre-test was given before to see the students’ mastery of vocabulary, before teaching them through picture, and the post-test was given to see the achievement in comprehending the material, after treatment or after teaching them through picture.The data were analyzed after each of the process (pre-test) was done. The result of the tests put in the tables to see the frequency distribution of the tests. Mean and standard deviation are computed for each of the tests.The mean score pre test is 29.66 and the mean score of post-test is 53.33 which means that the result of the post-test is higher than pre-test.The result of the pre-test indicates that the students’ ability in understanding and using vocabulary poor (low) before applying picture.The result of post-test indicates that the students’ ability in understanding and using vocabulary by applying picture is increased. It means that this technique is appropriate to be applied in teaching vocabulary